What are the priorities for improving quality for community pharmacy professional services? Nominal group technique discussions with multiple stakeholders - Ali M. K. Hindi; Ellen I. Schafheutle; Stephen M. Campbell (BMC Health Services Research)
Abstract Background Healthcare systems globally are expanding community pharmacy services to meet patient needs and reduce healthcare costs. In England this includes helping community pharmacies to provide integrated professional services but concerns persist over quality of care. This study aimed to identify priorities from key stakeholders for improving the quality of professional community pharmacy services. Methods Six homogenous nominal group (NG) discussions (face-to-face and online) involved 36 participants from diverse stakeholder backgrounds. Participants included patients (n = 10), community pharmacists (n = 7), general practitioners, a general practice-based pharmacist (n = 4), community pharmacy service regulators (n = 5), Community Pharmacy England members (n = 4), and Local Pharmaceutical Committee members (n = 6), both responsible for negotiating services. Delbecq’s NG technique included silent idea generation, round-robin feedback, discussion, and ranking for consensus building. Discussions were audio-recorded and verbatim transcripts analysed thematically using NVivo12. Emerging themes across all NGDs were analysed by thematic analyses. Individual discrete ranking within each NGD were then combined by summing the mean scores of the categories within each theme. Results Five key themes emerged from qualitative analysis across all NGDs: quality service design, sustained funding, integration with the wider healthcare system, positioning community pharmacy as a hub for patient needs, and adequate workforce training, optimising staffing and retention. Participants emphasised the need for long-term commitment to quality service design centred on addressing local patient need, sustained and predictable funding. Community pharmacy staff having some access to patient records for making informed clinical decisions was discussed. Scoring priorities ranked as follows (highest to lowest): ensuring quality service design, sustained funding, integration with healthcare systems, community pharmacy as patient hubs, and workforce training and retention, reflecting different stakeholder priorities in these areas. Conclusion This study highlighted core priority areas for a framework to improve the quality of community pharmacy professional services within a more responsive and integrated primary care led healthcare system.